Smallholdings with high oil palm yield also support high bird species richness and diverse feeding guilds - A. Razak, Syafiq; Saadun, Norzanalia; Badrul Azhar, .; Lindenmayer, David B. (Institute of Physics Publishing, 2020)
Biodiversity has been devastated globally in the past hundred years, largely because of land conversion and agricultural intensification. Conversion of tropical forest to oil palm plantations is one of the greatest per unit area contributors to biodiversity loss in Southeast Asia. Concerned consumers, mainly from developed countries, have begun demanding sustainable palm oil in response to these issues. More 'biodiversity-friendly' oil palm production is also in demand, similar to that of other commodity crops (e.g. coffee, cacao). However, farming practices that improve biodiversity are thought to reduce yield, leading to increased pressure to clear more forest, resulting in further biodiversity loss. Here, we explore relationships between oil palm yield and avian biodiversity. To gather data on yields and agricultural inputs, we interviewed smallholders in Selangor, Peninsular Malaysia. We also quantified bird species richness, feeding guild diversity, abundance, and vegetation structure in smallholdings. We found that smallholdings with high yields were characterised by high species richness and feeding guild diversity, but low bird abundance. Our empirical results show the benefits to both yield and avian biodiversity of a wildlife-friendly strategy in smallholdings. We encourage the integration of farming practices with management that improves biodiversity to reconcile oil palm production and nature conservation.